A Resting State Functional Magnetic Resonance Imaging Study of Unmedicated Adolescents With Non-suicidal Self-Injury Behaviors: Evidence From the Amplitude of Low-Frequency Fluctuation and Regional Homogeneity Indicator - Zhou, Yi; Yu, Renqiang; Ai, Ming; Cao, Jun; Li, Xiao; Hong, Su; Huang, Qian; Dai, Linqi; Wang, LiXia; Zhao, Lin; Zhang, Qi; Shi, Lei; et al. (Frontiers in Psychiatry, 2022)
Background Non-suicidal self-injury (NSSI) behaviors are common in adolescents with major depressive disorder (MDD). Brain studies specifically targeting adolescents with MDD and NSSI may provide new insights into suicide warnings in adolescents with MDD. Methods This study examined the whole-brain neural activity in adolescents aged between 12–17 years, 50 unmedicated MDD patients with (nsMDDs) or without NSSI (nnsMDDs), and 25 healthy controls (HCs) participated in this study, and analyzed the correlation between the values of amplitude of low-frequency fluctuation (ALFF), fractional amplitude of low-frequency fluctuation (fALFF) and regional homogeneity (ReHo) in significantly different brain regions and the scores of the relevant clinical psychological scale. Results Compared with nnsMDDs, nsMDDs had enhanced ALFF values in left middle occipital gyrus and left median cingulate and paracingulate gyri; the fALFF values of the right caudate nucleus was weakened in the nsMDDs; the ReHo values of right middle occipital gyrus and right middle temporal gyrus weakened and the ReHo values of right medial cingulate gyrus enhanced in nsMDDs. And all of differences were statistically significant. In nsMDDs, the value of ALFF in the left calcarine fissure and surrounding cortex was negatively correlated with the score of Children's depression Inventory (CDI); the value of fALFF in the right caudate nucleus was positively correlated with the score of Beck Scale for Suicidal Ideations (BSSI); the value of ReHo in the right middle temporal gyrus was positively correlated with the score of Multidimensional Anxiety Scale for Children (MASC); and the value of ReHo in the right median cingulate and paracingulate gyri was negatively correlated with the score of BSSI. Conclusions We found that in ALFF, fALFF and ReHo, the significant differences between nsMDDs and nnsMDDs are mainly located in default mode network (DMN) and visual network (VN), and there may be brain regions related to NSSI in DMN and VN. The significant differences brain regions in ALFF, fALFF and ReHo between nsMDDs and nnsMDDs were related to the total score of the relevant clinical psychological scale, and may be related to NSSI.